2004
DOI: 10.1128/aac.48.11.4113-4119.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Two Novel Macrolides, GW 773546 and GW 708408, Compared with Those of Telithromycin, Erythromycin, Azithromycin, and Clarithromycin against Haemophilus influenzae

Abstract: The MIC at which 50% of strains are inhibited (MIC 50 ) and the MIC 90 of GW 773546, a novel macrolide, were 1.0 and 2.0 g/ml, respectively, for 223 ␤-lactamase-positive, ␤-lactamase-negative, and ␤-lactamasenegative ampicillin-resistant Haemophilus influenzae strains. The MIC 50 s and MIC 90 s of GW 708408, a second novel macrolide, and telithromycin, an established ketolide, were 2.0 and 4.0 g/ml, respectively, while the MIC 50 and MIC 90 of azithromycin were 1.0 and 2.0 g/ml, respectively. The MIC 50 and MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…When LBM415 was tested against 130 ampicillin-resistant strains, the MIC range was 0.5 to 32 g/ml, with an MIC 50 of 2 g/ml and an MIC 90 of 8 g/ml. The results for other compounds were the same as those found in other studies (6,10,16,21). Time-kill analyses showed LBM415 to be more bactericidal against H. influenzae than has been reported for pneumococci and staphylococci (7,13,15).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…When LBM415 was tested against 130 ampicillin-resistant strains, the MIC range was 0.5 to 32 g/ml, with an MIC 50 of 2 g/ml and an MIC 90 of 8 g/ml. The results for other compounds were the same as those found in other studies (6,10,16,21). Time-kill analyses showed LBM415 to be more bactericidal against H. influenzae than has been reported for pneumococci and staphylococci (7,13,15).…”
Section: Discussionsupporting
confidence: 77%
“…A minimum of 14 passages were performed in each case, unless a Ͼ4-fold increase in the MIC was seen, in which case subculturing in the presence of antibiotic ceased. It is important to realize that the latter criterion, in view of the lack of susceptibility breakpoints for LBM415, was arbitrarily based upon our previous studies (3,21). The maximal number of passages was 50.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 To develop novel potent ketolides, a variety of structural modifications of the ketolide core skeleton have been carried out. Recently, many ketolide derivatives such as 6-O-alkyl ketolides, [14][15][16][17][18][19] 9-oxime macrolides, [20][21][22][23][24][25] 11,12-cyclic carbamate ketolides, [26][27][28][29][30][31][32] 13-substituents ketolides and 6,11-bridged ketolides [33][34][35] with excellent activities toward numerous macrolide-resistant pathogens were obtained. Herein, we described the synthesis and in vitro biological evaluation of a set of novel ketolides bearing an aryltetrazolyl-substituted alkyl side chain.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have demonstrated that telithromycin MICs were equal to or at least 1 dilution higher than those of azithromycin (24). Telithromycin activity against H. influenzae is, however, superior to that of erythromycin and clarithromycin (14). MICs and breakpoints of macrolides, azalides, and ketolides against this organism must be considered together with their raised levels in tissue and epithelial lining fluids, which may improve their clinical efficacy in treatment of pneumonia (28).…”
mentioning
confidence: 99%